The EATWELL project: Recommendations for healthy eating policy interventions across Europe. Issue 3 (16th August 2013) - Traill, W. B.; Mazzocchi, M.; Niedźwiedzka, B.; Shankar, B.; Wills, J.
Summary The EATWELL research project (www.eatwellproject.eu) (Interventions to Promote Healthy Eating Habits: Evaluation and Recommendations) funded by the European Commission aimed to improve nutrition policy in Europe by providing scientifically sound evidence on the effectiveness of past healthy eating interventions. This interdisciplinary project involved academic partners from 5 European Union countries and 10 partners in all. As a first step, the project identified 121 large‐scale policy interventions in European countries over the period 1990–2010 and any existing evidence on their evaluation. Of these policies, 82 were aimed at supporting informed choices, and the remaining 39 sought to change the market environment by enhancing the availability of healthier foods, restricting the availability of less healthy foods or nutrients, or changing relative food prices through food taxes or subsidies. Subsequently, advanced quantitative evaluation models were used to conduct a fresh analysis of a small selection of these policy case studies, based on secondary data. Based on these evaluations, together with garnered public and stakeholder opinion, the project put forward proposals for future healthy eating policies, improved evaluation methods and the collection of better data.